RISK FACTOR DISTRIBUTION AND LONG-TERM OUTCOMES IN YOUNG PATIENTS UNDERGOING PERCUTANEOUS CORONARY INTERVENTION IN MACEDONIA - Zafirovska Biljana; Otljanska, Magdalena; Petkoska, Danica; Kedev, Sashko (Sestre Milosrdnice University Hospital Center (KBC Sestre milosrdnice), 2019)
The aim was to assess coronary artery disease (CAD) risk factor distribution and long-term outcomes in young patients undergoing percutaneous coronary intervention (PCI) in Macedonia. A total of 12,361 PCI patients (from March 2011 to December 2017) were included in the study. Group 1 included 309 young patients aged ≤40 as the main study group, comparing them to 12,052 older PCI patients (group 2) during the study period. We compared CAD risk factor distribution, clinical and procedure characteristics. Additionally, angiographic data, long-term major adverse cardiac and cerebrovascular events (MACCE) and mortality were analyzed in group 1 patients. Median age was 36±4 years in group 1 and 62±11 years in group 2. Male patients predominated in both groups (88% vs.73%). Positive family history for CAD, smoking and obesity was much more common in the young group (p<0.0001). ST segment elevation myocardial infarction (STEMI) primary PCI was also more frequent with 48% of PCI in the young group (p<0.0001). Multivessel CAD and chronic total occlusion interventions were more common in the older group (51% and 28%, respectively; p<0.0001). Procedure duration (31±0.4 vs. 35±22 min) and fluoroscopy time (9±4 vs. 9±12 min) were similar in both groups. There was no difference in access site bleeding (4.8% vs. 4.3%). During the 3.5-year median follow up, MACCE was present in 1.9% of young patients. In conclusion, positive family history for CAD, obesity and smoking were the most common risk factors in the young PCI population. Young PCI patients usually had single vessel CAD with STEMI being more frequent as the cause for primary PCI. Long-term annual survival exceeded 99% in these patients with excellent prognosis after PCI.